Ceramic lined steel pipe production using SHS method - Raza, R.G.; Mohd, H.I. (2009)
Self-Propagating High-Temperature Synthesis (SHS) or combustion synthesis (CS) is an advanced method for producing high temperature materials such as refractory materials, intermetallics, and cermets. Combustion synthesis is characterized by extremely heating rate, high temperatures, and short reaction times. Centrifugal force densification was employing to produce dense ceramic-lined steel pipes. The centrifugal force facilitates phase separation of multi-component products during the process. In this research the SHS-centrifugal machine was designed to produce a ceramic-lined steel pipes from Fe2O3 – Al powder mixture. The pipe inner diameter of the steel pipes were 70 mm and the centrifugal acceleration was reached to a = 350g. Thermit reaction of Fe2O3 and Al was occurred inside the pipe to produce Al2O3 ceramic in the innermost layer and Fe layer at a region between the outer steel pipe and the ceramic layer.